Hubungan Pengetahuan Ibu Hamil Trimester II-III Tentang Senam Hamil Dengan Melakukan Senam Hamil - Eka Deviany Widyawaty (NERSMID : Jurnal Keperawatan dan Kebidanan, 2018)
Pregnancy causes physical, as well as emotional changes from the mother and social changes in the family. Pregnancy exercises is known both for the health of the mother and the fetus she contains. The purpose of the study was to determine the relationship of knowledge of pregnant women in trimester II-III about pregnancy exercise by doing pregnancy exercises.This type of research is analytic with cross sectional design. Samples were taken with the technique of Non-Probability: Purposive Sampling of 44 respondents. Independent variable is the knowledge of pregnant women in trimester II-III about pregnancy exercise while the dependent variable is doing pregnancy exercise. Data collection using a questionnaire. The results showed that of 44 respondents (73%) who had good knowledge and did pregnancy exercise as many as 28 pregnant women (63.6%), 9 respondents (20%) who had enough knowledge to do pregnancy exercises as much as 2 pregnant women ( 4.5%), and 3 respondents (7%) who had less knowledge none of them did pregnancy exercise. The results of the study based on the Chi-Square test results obtained value ρ value = 0,000 at the significance level α = 0.05. So that H0 is rejected, meaning that there is a relationship between Knowledge of Trimester II-III Pregnant Women. About Pregnancy Exercises by Pregnancy exercise. Based on the description above, it can be concluded that knowledge affects pregnant women in performing pregnancy exercises.